PROGNOSING OF CHRONIC RENAL FAILURE DEVELOPMENT AT THE HEMATURIC FORM OF CHRONIC GLOMERULONEPHRITIS IN CHILDREN - Borysova, T.; Lytvynova, O. (Ukrainian Journal of Nephrology and Dialysis, 2017)
Purposeofresearch: studying of frequency of chronic renal failure development (CRF) depending on the duration of hematuric form of chronic glomerulonephritis (HFHGN), revealing of unfavorable disease outcome factors and development of mathematical model to forecast the CRF forming. Methods. Retro- and prospective analysis of nephrological examination results in patients was performed in the debut of glomerulonephritis (95 children), at duration of HFCGN less than 5 years (95 children), from 6 until 10 years (65 children), more than 10 years (45 patients). Intravital morphological research of renal tissue was carried out in 43 patients. Results.The relative value of CRF occurrence intensity at duration of HFCGN less than 5 years was 3,6, from 6 until 10 years - 8,9, more than 10 years - 24,2 cases for 100 patients-years. Mainly CRF of the first stage developed. Unfavorable prognostic factors of HFCGN course were family history of nephropathy, proteinuria, АH, loss of cortico-medullary differentiation in kidneys according to ultrasonic research data, increase of creatinine in blood serum, presence of hyalinosis and sclerosis in glomuluses, macrofocal infiltration of interstitium. Conclusions. Prognostic mathematical models depending on the duration of HFCGN and on the data of intravital morphological research of renal tissue are developed.